Radiation defects manipulation by ultrasound in ionic crystals - Ostrovskii, I.; Ostrovskaya, N.; Korotchenkov, O.; Reidy, J. (IEEE transactions on nuclear science, 2005)
The radiation-induced optical absorption in ionic crystals is remarkably removed by a room-temperature ultrasonic treatment of the crystals. It is shown that the effect can be explained by defect migration processes occurring in ultrasonic fields. The experimental results display features consistent with a recent theory of the quantum diffusion. This new method of a cold annealing of radiation defects in solids can be termed as ultrasonic defect manipulation